Voice in French corporate training: A critical issue in developing employee capability. (May 2020) - Subramanian, Dilip; Zimmermann, Bénédicte
The article discusses the impact of organizational configurations on employees' training capabilities. Inspired by the capability approach, it uses qualitative data to question under what organizational conditions firms in France provide their employees with the opportunities and means to participate not just in training programmes, but in those programmes they have reason to value. The results suggest the existence of three different training models – skill-updating, skill-developing and capability-enhancing – depending on the choice processes involved, the importance they accord to employee agency, and the training outcomes. While human resource policies offering training opportunities are important in French organizations, enabling individual capability ultimately depends on employee participation schemes. The article further argues that this goal cannot be achieved through collective voice alone; in vocational training, individual voice plays an equally central role.